Gambaran hingga tatalaksana COVID-19 pada anak - Marissa Leviani Hadiyanto (DiscoverSys Inc., 2021)
Background: Coronavirus disease (COVID-19) caused by the SARS-CoV-2 virus started in Wuhan, China, spreading rapidly to various countries. This literature review aims to provide an overview, diagnosis and management of COVID-19 in children.Methods: In this paper, the literature review method is used. Sources of reading come from relevant and appropriate journals and books from PubMed, Ebsco and Proquest.Results: Based on data from the Indonesian Ministry of Health dated January 15, 2021, it shows that 2.7% of confirmed cases of COVID-19 are children aged 0-5 years, and 8.9% children aged 6- 18 years. The mortality rate for COVID-19 in children aged 0-5 years is 0.8% and aged 6-18 years is around 1.5%. The most common pattern of transmission of COVID-19 to children is from family clusters. Symptoms and signs of COVID-19 in children include fever, cough, rhinorrhea, painful swallowing, weakness, lacrimation, headache, diarrhea, vomiting, cyanosis and in severe cases Multisystem Inflammatory Syndrome COVID-19 (MIS-C). Diagnosis of COVID-19 in children is confirmed from clinical symptoms and supportive laboratory results such as low to normal leukocytes, increased CRP and radiological abnormalities such as hazy opacities on X rays and ground glass appearance on thoracic computed tomography (CT), despite Real Time Polymerase Chain Reaction ( RT-PCR) is the standard method for diagnosing this disease. General management of children with COVID-19 in the form of complete rest, supportive therapy, symptomatic therapy, administration of vitamins and monitoring of vital signs and oxygen supplementation. Antiviral therapy, antibiotics and steroids are given as indicated. The COVID-19 vaccine for children is currently in the process of being researched.Conclusion: The COVID-19 pandemic is spreading rapidly, and confirmed cases in children are increasing significantly. The prevalence of COVID-19 in children tends to be lower and most of them have milder symptoms than adults, but proper diagnosis and management is needed. Latar Belakang: Coronavirus disease (COVID-19) disebabkan oleh virus SARS-CoV-2 diawali di Wuhan, Cina menyebar dengan cepat ke berbagai negara. Tinjauan pustaka ini bertujuan memberikan gambaran, diagnosis dan tatalaksana COVID-19 anak.Metode: Dalam penulisan ini digunakan metode tinjauan pustaka. Sumber bacaan berasal jurnal-jurnal dan buku relevan dan sesuai dari PubMed, Ebsco dan Proquest.Hasil: Berdasarkan data Kementrian Kesehatan Indonesia tanggal 15 Januari 2021 menujukkan 2,7 % kasus terkonfirmasi COVID-19 adalah anak usia 0-5 tahun, dan 8,9% anak usia 6- 18 tahun. Angka Kematian COVID-19 pada anak usia 0-5 tahun adalah 0,8% dan usia 6-18 tahun sekitar 1,5%. Pola tersering penularan COVID-19 pada anak adalah berasal dari kluster keluarga. Gejala dan tanda COVID-19 pada anak meliputi demam, batuk, rhinorrhea, nyeri menelan, lemas, lakrimasi, nyeri kepala, diare, muntah, sianosis dan pada kasus berat terjadi Multisystem Inflammatory Syndrome COVID-19 (MIS-C). Diagnosa COVID-19 anak ditegakkan dari gejala klinis dan hasil laboratorium mendukung seperti leukosit yang rendah ke normal, peningkatan CRP dan abnormalitas radiologis seperti hazy opacities pada X ray dan ground glass appearance pada Computed Tomography (CT) toraks, meskipun Real Time Polymerase Chain Reaction (RT-PCR) merupakan metode baku untuk menegakkan diagnosis penyakit ini. Tatalaksana umum pasien COVID-19 anak berupa istirahat total, terapi suportif, terapi simtomatik, pemberian vitamin serta pemantauan tanda vital dan suplementasi oksigen. Terapi antivirus, antibiotik, dan steroid diberikan sesuai indikasi. Vaksin COVID-19 anak saat ini masih dalam proses penelitian.Kesimpulan: Pandemi COVID-19 meyebar dengan cepat, dan kasus terkonfirmasi pada anak meningkat secara signifikan. Prevalensi COVID-19 anak cenderung lebih rendah dan sebagian besar memiliki gejala yang lebih ringan dibanding dewasa namun diagnosis dan tatalaksana yang tepat sangat diperlukan.